Single-dose TB-402 or rivaroxaban for the prevention of venous thromboembolism after total hip replacement - Verhamme, Peter; Gunn, Sophie; Sonesson, Elisabeth; Peerlinck, Kathelijne; Vanassche, Thomas; Vandenbriele, Christophe; Ageno, Walter; Glazer, Steven; Prins, Martin; Buller, Harry; Tangelder, Marco (Thrombosis and Haemostasis, 2013)
TB-402 is a long-acting monoclonal antibody that partially inhibits factor VIII. A single administration of TB-402 was effective and well-tolerated for the prevention of venous thromboembolism (VTE) after total knee replacement. In this study, the efficacy and safety of a single administration of TB-402 for the extended prophylaxis of VTE after total hip replacement (THR) was investigated. This was a phase II, randomised, active-controlled, double-blind study that included patients undergoing elective THR surgery. Patients were randomised to TB-402 25 mg or TB-402 50 mg, administered as a single intravenous administration 2–4 hours postoperatively, or to rivaroxaban 10 mg once daily for 35 days. The primary efficacy outcome was total VTE defined as symptomatic VTE and asymptomatic deep-vein thrombosis (DVT) detected by bilateral venography at day 35. The principal safety outcome was the incidence of major bleeding and clinically relevant non-major bleeding until day 35. Total VTE was similar in all groups: 5.3% (95%CI 2.9–9.6), 5.2% (95%CI 2.8–9.3) and 4.7% (95%CI 2.5–8.7) for TB-402 25 mg, TB-402 50 mg and rivaroxaban, respectively. All were asymptomatic DVTs. Major or clinically relevant non-major bleedings were observed in 5.8% (95%CI 3.3–9.9), 7.2% (95%CI 4.4–11.6) and 1.4% (95%CI 0.5–4.2) for TB-402 25 mg, TB-402 50 mg and rivaroxaban, respectively. In conclusion, TB-402, administered as a single postoperative dose, had a similar efficacy compared to rivaroxaban for the prevention of VTE after THR. The incidence of major and clinically relevant non-major bleeding was higher in the TB-402 groups than in the rivaroxaban group.
Keywords: Factor VIII; TB-402; rivaroxaban; venous thromboembolism; thrombo-prophylaxis; deep-vein thrombosis; total hip replacement